Women at their work - English, Betty Lou (New York Dial Press, 1977)
Twenty-one women, including a jockey, an orchestra conductor, a radio interviewer, chemist, firefighter, judge, carpenter, and rabbi, briefly discuss their work.
1
Keywords: Vocational guidance for women -- Juvenile literature